First record of the genus Trispinaria Quicke, 1986 (Hymenoptera, Braconidae, Braconinae) in Vietnam, with descriptions of two new species - Oanh, Nguyen Thi (Zookeys, 2020)
Two new species of the genus Trispinaria Quicke, 1986, from Vietnam, viz. T. seminigra Long, sp. nov. and T. vietnamica Long, sp. nov., are described and fully illustrated. Additionally, this is the first record of the genus Trispinaria in Vietnam. A checklist with distributions of previously described species of the genus Trispinaria is given. Comparative characters of the Vietnamese species are provided and modified key couplets are provided to facilitate their identification.